A PESTEL and SWOT impact analysis on renewable energy development in Togo - Kansongue, Nanimpo; Njuguna, James; Vertigans, Stephen (Frontiers in Sustainability, 2023)
Like most developing countries, Togo continues to rely on the use of traditional forms of biomass energy which causes tremendous socio-economic, environmental and health hazards. In addition, the imbalanced distribution and use of electricity, petroleum and liquid gas reflect the disproportion in income and quality of life. This paper highlight the development renewable energy in the past decade and the challenges facing the Togolese government. Framework approach such as PESTEL and SWOT analysis were utilised to assess both the internal and external factors in relation to renewable energy development and its impact on Togo. It provides a better understanding of the sustainability issues facing Togo and relevant solutions on the best methods leading to greater impact and development. The result shows that renewable energy development in Togo has improved in the past decade and had some impact on the socio-economic development. However better development will be achieved if sustainable approaches are introduced to provide a long-term solution to the high capital costs of the technologies, institutional sustainability is incorporated, the number of trained personnel and technical expertise has increased in addition to the Government engagement with funding bodies to secure funds that will favour off-grid and poorest communities is on the rise. There is also a need to include local participation in the design and operation of projects, introduce cross-subsidization tariff scheme that cover the operation and maintenance cost of off-grid solar PV users that will favour poor households. Finally, liberalization of the energy sector is needed as well as government’s support to help private investment in rural electrification through Build-Own-Operate arrangements.